Cultural assimilation among Malays and Indians in Malaysia - Punitha, S.; Kumaran, S. (2014)
This research is about the cultural elements assimilated within Malays and Indians in Malaysia. The cultural elements are including language, literature, roles and statuses of king, women, poets and Brahmins, beliefs & ideologies and customs & traditions. The scholar Munsyi Abdullah's texts were chosen to identify and analyse the Malays cultural practices because he is the father of Malay modern literature in Malaysia. He had literate his books with historical truths. Besides that, Texts of Tamil classical literature also were chosen to identify and list out the Indians cultural habits. The Tamil classical texts were compiled some 2500 years ago in India and it witnesses the Tamils signified the cultural practices in their daily life. The majority of the Malays in Malaysia recognized as Malay descendants by their mother tongue which is the Malay language. Indians had been visiting Malaya as traders and merchants for over 2000 years, but they did not settle down here as settlers until 19th century. The formation of Malaysia under British colonization with multi races of people encourages a good integration among Malays and Indians and therefore there was a chance for them to adapt and assimilate each other's cultural element.